Upaya Orangtua Dalam Mencegah Kecanduan Merokok Pada Remaja - Muhammad Alridho Lubis; San Putra; Ega Ayuningtyas; Rezika Pratiwi; Muhammad Alridho Lubis (Program Studi Bimbingan dan Konseling FKIP UMSU, 2022)
Adolescence is a period of age transition from children to adults where at this time adolescents tend to experience emotional instability and instability of changes in themselves. Adolescents are at the age of self-discovery, so they tend to be more sensitive and feel like they want to be recognized. This study uses a qualitative approach with the case method. The results showed that teenagers who became smokers tended to smoke because of their social and friendly environment. If adolescent smokers have parents and a non-smoker family environment, they will feel more reluctant to smoke in the family environment. Adolescents do smoking activities because they feel like they want to be recognized and they feel that by smoking they are more recognized in their social environment. Parents can communicate interaction or two-way communication as an effort to prevent smoking addiction in adolescents. Communicating without cornering or blaming teens will be easier for teens to accept because they feel valued.